Preparation of refractory calcium aluminate cement using the sonochemical process - LOURENÇO, Rafaela Roberta (2013)
Calcium aluminate cements (CAC) were prepared using the sonochemical process, followed by heat treatment. A study was made of the action of ultrasonic waves and the influence of thermal treatment conditions on two initial molar compositions of 1:1 and 1:2 of calcia:alumina. The aqueous suspension containing the raw materials (A-50 alumina and CaO) was subjected to an ultrasonic bath, followed by drying and burning at 1000, 1200 and 1300 ºC. These cements were characterized by SEM, XRD and the mechanical strength was evaluated by splitting tensile tests, using commercial cement as a reference. Furthermore, the phases were semi-quantified using the Rietveld method. The results show that hydration and sonochemical action increased the reactivity of the raw materials during firing and that phase formation is dependent on the thermal treatment conditions. The CAC cements were obtained at temperatures at least 200 ºC lower than those used in conventional methods, indicating the potential of this route of synthesis.